COMPARATIVE STUDY OF EARLY MIOCENE VOLCANISM IN SAKHALIN AND EARLY-MIDDLE MIOCENE VOLCANISM IN THE EASTERN SIKHOTE-ALIN RANGE: LOCATION, AGE, AND PETROGRAPHY OF EARLY MIOCENE VOLCANIC ROCKS IN SAKHALIN - Shilov V.N. (My University, 1999)
The Early Miocene volcanic rocks of Sakhalin, constituents of the Chekhov Formation, are separated from the older Late Paleogene volcanics (phase I of Cenozoic volcanism) by a thick normal sedimentary sequence and, hence, attributed to phase II of Cenozoic volcanism. These volcanics occur in scattered localities at the western and eastern Sakhalin coast and on Moneron Island in the Sea of Japan near the SW end of Sakhalin. The dominant rocks are basalts and basaltic andesites; less common are andesites, dacites and rhyolites being found in a few localities.
Keywords: Miocene; Cenozoic::Neogene::Miocene; Кайнозой::Неоген::Миоцен